Short-term high-intensity interval exercise training attenuates oxidative stress responses and improves antioxidant status in healthy humans - Bogdanis, G.C.a; Stavrinou, P.a; Fatouros, I.G.b; Philippou, A.c; Chatzinikolaou, A.b; Draganidis, D.b; Ermidis, G.b; Maridaki, M.a (Food and Chemical Toxicology, 2013)
This study investigated the changes in oxidative stress biomarkers and antioxidant status indices caused by a 3-week high-intensity interval training (HIT) regimen. Eight physically active males performed three HIT sessions/week over 3. weeks. Each session included four to six 30-s bouts of high-intensity cycling separated by 4. min of recovery. Before training, acute exercise elevated protein carbonyls (PC), thiobarbituric acid reactive substances (TBARS), glutathione peroxidase (GPX) activity, total antioxidant capacity (TAC) and creatine kinase (CK), which peaked 24. h post-exercise (252 ± 30%, 135 ± 17%, 10 ± 2%, 85 ± 14% and 36 ± 13%, above baseline, respectively; p<. 0.01), while catalase activity (CAT) peaked 30. min post-exercise (56 ± 18% above baseline; p<. 0.01). Training attenuated the exercise-induced increase in oxidative stress markers (PC by 13.3 ± 3.7%; TBARS by 7.2 ± 2.7%, p<. 0.01) and CK activity, despite the fact that total work done was 10.9 ± 3.6% greater in the post- compared with the pre-training exercise test. Training also induced a marked elevation of antioxidant status indices (TAC by 38.4 ± 7.2%; CAT by 26.2 ± 10.1%; GPX by 3.0 ± 0.6%, p<. 0.01). Short-term HIT attenuates oxidative stress and up-regulates antioxidant activity after only nine training sessions totaling 22. min of high intensity exercise, further supporting its positive effect not only on physical conditioning but also on health promotion. © 2013 Elsevier Ltd.